2015
DOI: 10.1117/1.jmi.2.4.041006
|View full text |Cite
|
Sign up to set email alerts
|

Associating spatial diversity features of radiologically defined tumor habitats with epidermal growth factor receptor driver status and 12-month survival in glioblastoma: methods and preliminary investigation

Abstract: Abstract. We analyzed the spatial diversity of tumor habitats, regions with distinctly different intensity characteristics of a tumor, using various measurements of habitat diversity within tumor regions. These features were then used for investigating the association with a 12-month survival status in glioblastoma (GBM) patients and for the identification of epidermal growth factor receptor (EGFR)-driven tumors. T1 postcontrast and T2 fluid attenuated inversion recovery images from 65 GBM patients were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…For example, enhanced T 1 WI could show the perfusion and extravasation characteristics of the contrast agent, while T 2 MRI sequences present edema as well as cell density, to a certain extent . T 1 WI spatial habitat diversity features have previously been demonstrated to be associated with clinical characteristics of epidermal growth factor receptor . This may also explain why more enhanced T 1 WI features were selected than the other two sequences in the combination radiomic features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, enhanced T 1 WI could show the perfusion and extravasation characteristics of the contrast agent, while T 2 MRI sequences present edema as well as cell density, to a certain extent . T 1 WI spatial habitat diversity features have previously been demonstrated to be associated with clinical characteristics of epidermal growth factor receptor . This may also explain why more enhanced T 1 WI features were selected than the other two sequences in the combination radiomic features.…”
Section: Discussionmentioning
confidence: 99%
“…39 T 1 WI spatial habitat diversity features have previously been demonstrated to be associated with clinical characteristics of epidermal growth factor receptor. 40 This may also explain why more enhanced T 1 WI features were selected than the other two sequences in the combination radiomic features. Multiparametric MRI combines contrast sequences that might illuminate hidden characteristics and offer insight into molecular status related to tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 48 image‐guided biopsies obtained in 13 tumors, Hu et al demonstrated correlations between conventional, diffusion tensor imaging (DTI), and dynamic susceptibility contrast (DSC) perfusion metrics, and commonly implicated alterations in EGFR, PDGFRA, PTEN, CDKN2A, RB1, and TP53 ( P < 0.03)—with accuracies ranging from 87.5% for RB1 to 37.5% for TP53. A similar study of spatial diversity texture features was able to characterize local EGFR mutation status as well as patient survival in 65 glioblastomas . Because the various clonal populations are driven by unique genomic alterations, each with inherently different sensitivities to treatment, accurate characterization of tumor heterogeneity will become essential for success in the emerging era of targeted cancer therapies.…”
Section: Brainmentioning
confidence: 99%
“…A similar study of spatial diversity texture features was able to characterize local EGFR mutation status as well as patient survival in 65 glioblastomas. 35 Because the various clonal populations are driven by unique genomic alterations, each with inherently different sensitivities to treatment, accurate characterization of tumor heterogeneity will become essential for success in the emerging era of targeted cancer therapies.…”
Section: Predicting Molecular and Genomic Alterations And Survivalmentioning
confidence: 99%
“…To predict outcomes, habitat images have been generated based on postcontrast T1 and FLAIR sequences. 191 An emerging area of interest considers the use of PET data in combination with CT or MRI to identify habitats with distinct combinations of metabolic activity (PET) with cellularity or perfusion (MRI). Then, FLAIR values were added, thus classifying the images into 5 habitats according to different combinations of blood flow and cellularity.…”
Section: Habitat Imagingmentioning
confidence: 99%